Intervención De Enfermería En La Redirección De Catéteres Tenkhoff Disfuncionales - Durán, Rigoberto Díaz; Contreras, Yuliana Nieto; Cruz, Armando Miranda de la; Torres, Clara Acosta; Gómez, Sergio Quiroz; Olán, Lorena Magaña (European Scientific Journal, ESJ, 2018)
Renal Diseases (RD) today represent a high social and economic cost that affects the quality of life of people. This is irrespective of the fact that there are Substitutive Therapies of Renal Function (STRF) in some complications such as migration, elbowing or plug of fibrin in Peritoneal Dialysis. Objective: To know the effectiveness of the nursing intervention in the redirection of dysfunctional Tenckhoff catheters installed in the General Subzone Hospital No. 4 of the IMSS of the municipality of Tenosique, Tabasco, Mexico. Methodology: This uses a quantitative-qualitative approach with the quasi-experimental longitudinal cut design, with n = 9 people with CKD in TSFR under the DPCA and DPA modality. Results: The data that predominated indicate that 5 (55.6%) were men and 4 (44.4%) women. In terms of occupation, 3 were housewives (33.3%), followed by employees. 8 (88.9%) were married people and 4 (44.4%) have completed their basic primary education. 7 (77.8%) people have been diagnosed of Diabetes. At the pre-intervention stage, they found signs of edema, uremic syndrome, elevated creatinine, hyperglycemia and fluid control with a positive balance sheet. That is to say that the peritoneal cavity was presenting retention of peritoneal fluid, which is confirmed by the simple X-ray photography of abdomen. At the post-intervention stage, they found changes that result to decrease of the edema, urea, and creatinine due to the exit of the liquid preserved in the peritoneum. Conclusion: The redirection of the catheters Tenckhoff through the employment of the nursing intervention with metallic guide is effective to recover the functionality of the same one.